Development of a survey instrument to evaluate women's experiences of their maternity care. Issue 4 (July 2021) - Beecher, Claire; Drummond, Linda; Foley, Conor; White, Mark; Greene, Richard; Ryan, Ethel; O'Dwyer, Laura M.; Dowling, Maura; Devane, Declan
Abstract: Background: The process of developing a survey instrument to evaluate women's experiences of their maternity care is complex given that maternity care encapsulates various contexts, services, professions and professionals across the antenatal, intranatal and postnatal periods. Aim: To identify and prioritise items for inclusion in the National Maternity Experience Survey, a survey instrument to evaluate women's experiences of their maternity care in the Republic of Ireland. Methods: This study used an adapted two-phase exploratory sequential mixed methods design. Phase one identified items for possible inclusion and developed an exhaustive item pool through a systematic review, focus groups and one to one interviews, and a gap analysis. Phase two prioritised the items for inclusion in the final item bank through a Delphi study and consensus review. Findings: Following iterative consultation with key stakeholder groups, a bank of 95 items have been prioritised and grouped within eight distinct care sections; care during your pregnancy, care during your labour and birth, care in hospital after the birth of your baby, specialised care for your baby, feeding your baby, care at home after the birth of your baby, overall care and you and your household. Conclusion: Robust and rigorous methods have been used to develop a bank of 95 suitable items for inclusion in the National Maternity Experience Survey.